(untitled) (Educa Journal of Studies, 2026)
This article explores the literary significance of Mark Twain as one of the most influential figures in American literature. It examines his role in the development of realism, his distinctive use of humor and satire, and his contribution to the formation of American literary identity. Drawing on textual analysis of his major works, including Adventures of Huckleberry Finn and The Adventures of Tom Sawyer, the study highlights Twain’s innovative narrative techniques and social criticism. The article argues that Twain’s legacy lies in his ability to combine entertainment with profound ethical and cultural insights.